Serum cardiac troponin I concentrations decrease following treatment of primary immune‐mediated haemolytic anaemia. (2nd July 2015) - Cartwright, J. A.; Gow, D. J.; Gow, A. G.; Handel, I.; Reed, N.; Brown, A. J.; Cash, R.; Foote, A.; Mackenzie, D.; Bell, R.; Mellanby, R. J.
<x xml:space="preserve">Abstract</x> OBJECTIVES The measurement of serum cardiac troponin I concentrations in dogs with a range of non‐primary cardiac illnesses suggests that cardiac myocyte damage is commonplace. Dogs with primary immune‐mediated haemolytic anaemia have increased serum cardiac troponin I concentrations at the time of diagnosis. However, it is unclear whether biochemical evidence of cardiac myocyte damage improves following successful treatment of anaemia. METHODS A haematology profile was performed and serum cardiac troponin I concentrations were measured in 19 dogs with primary immune‐mediated haemolytic anaemia before and after treatment. RESULTS The haematocrit increased significantly (P = 0 · 0001) following treatment of primary IMHA (median pre: 0 · 13 L/L, median post: 0 · 33 L/L). The serum cardiac troponin I concentrations decreased significantly (P < 0 · 05) after treatment (median pre: 0 · 26 ng/mL, median post: 0 · 16 ng/mL). CLINICAL SIGNIFICANCE Serum cardiac troponin I concentration decreases following successful treatment of primary immune‐mediated haemolytic anaemia. The clinical and prognostic significance of serum cardiac troponin I concentrations before and after treatment in dogs with primary immune‐mediated haemolytic anaemia merits further investigation.